Maternal satisfaction during COVID-19 pandemic birthing: a cross-sectional study - Siti Zuhaida Hussein,; Mat Radzi S, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The birth pandemic has created major challenges to the quality and efficiency of health care systems, maternity care providers and women’s childbirth experiences. This study was conducted to determine maternal satisfaction with intrapartum care and its relationship with intrapartum mothers in a teaching hospital in Kuala Lumpur. This cross-sectional study was conducted with 300 intrapartum women using systematic random sampling. Maternal satisfaction was examined using 26-item questionnaires with a Cronbach’s alpha value of 0.88. Data were analysed using SPSS version 26. The results of this study showed that the majority of respondents were between the ages of 31 and 36 years, Malay, housewives (93.8%), had secondary education (93.1%), and had an income between RM4000 and RM4999 per month (97.6%). In addition, the results of the study found that 94.7% of respondents had a high level of satisfaction with intrapartum care, and 86.7% had a positive overall perception of intrapartum care. In addition, a weak but significant positive correlation was found between maternal satisfaction and mother’s perception of intrapartum nursing care (r = 0.371; p ≤ 0.001). Understanding the mother’s satisfaction with intrapartum care can help to optimise her well-being and prepare her for infant care.